Glenohumeral range of motion and stiffness in professional baseball pitchers - Borsa, P. A.; Dover, G. C.; Wilk, K. E.; Reinold, M. M. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study was conducted to perform kinematic measures in a group of asymptomatic professional baseball pitchers to determine side-to-side differences in passive glenohumeral range of motion (ROM) and stiffness. We hypothesized that the throwing shoulder in asymptomatic pitchers would display greater passive glenohumeral stiffness than the contralateral nonthrowing shoulder.